Digital Transformation of Zakat Platforms: The Role of Trust and Accountability in Muzaki’s Decisions to Pay Zakat Mal - Annisa Ambar Fajrin; Nurwinsyah Rohmaningtyas (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2026)
This study aims to analyze the role of trust and accountability in muzaki's decision to pay zakat mal through the transformation of the digital zakat platform at BAZNAS in Jombang Regency. This study uses a qualitative descriptive method with a case study approach. Data collection techniques were carried out through interviews, observations, and documentation, with data validity testing using source and technique triangulation. The results of the study indicate that the transformation of the digital zakat platform contributes to increasing trust and accountability in zakat management, thereby facilitating muzaki in fulfilling their zakat obligations effectively and efficiently. The trust of muzaki is reflected in the dimensions of ability, integrity, and benevolence, while accountability is demonstrated through transparent reporting, ease of access to information, and a transaction confirmation system in the perspective of Shari'ah Interprise Theory. Digital transformation also provides convenience and certainty for muzaki in the zakat payment process, thereby encouraging increased participation in the use of the digital zakat platform.